Effects of age, gender, ethnicity, diurnal variation and exercise on circulating levels of matrix metalloproteinases (MMP)-2 and -9, and their inhibitors, tissue inhibitors of matrix metalloproteinases (TIMP)-1 and -2 - Tayebjee, Muzahir H.; Lip, Gregory Y.H.; Blann, Andrew D.; MacFadyen, Robert J. (Thrombosis research, 2005)
Background: Circulating metalloproteinases (MMP) and their inhibitors (TIMP) are indices of vascular and cardiac tissue matrix turnover. However, the temporal changes and relationship of these parameters to age, gender, ethnicity and exercise have been poorly defined. We therefore studied these aspects on plasma levels of MMP-2 and -9 and TIMP-1 and -2, as the major metalloproteinases (and their inhibitors) implicated in pathophysiology of vascular disease. Methods: Venous citrated blood was collected from 93 normal healthy volunteers from four ethnic groups (Afro-Caribbean, South Asian, Caucasian and Far Eastern) for a cross-sectional study. In addition, 20 separate healthy volunteers were studied during supine rest, before and immediately following peak treadmill stress using a Bruce protocol. MMP-2 and -9 and TIMP-1 and -2 were all measured by ELISA. Results: There was a categorical distribution of MMP-2 concentration with individual subjects showing high levels, yet others being undetectable, although these changes were unrelated to age, gender or ethnicity. TIMP-1 and -2 showed a modest negative correlation with age ( r=−0.251, p=0.015; r=−0.254, p=0.014). There was a positive correlation between MMP-2 and TIMP-2 ( r=0.399, p<0.001), MMP-9 and TIMP-1 ( r=0.45, p<0.001) and between TIMP-1 and TIMP-2 ( r=0.275, p=0.008). When adjusted for age and gender, there were no significant differences in MMP-2 and TIMP-1 and -2 between the four ethnic groups. MMP-9 was significantly lower in the Far Eastern group compared to the other three ethnic groups ( p=0.012). Only TIMP-1 ( p=0.042) and TIMP-2 ( p=0.024) were significantly altered after exercise. ConclusionAge and exercise both have modest effects on circulating concentrations of TIMP-1 and-2. MMP-9 appears lower in individuals of Far Eastern/Chinese origin regardless of age or gender. The positive association between MMPs and TIMPs suggests that in healthy individuals, enzyme activity may be regulated by this interaction. The reasons for the categorical distribution of MMP-2 remain unclear but this would be important in any studies designed to use circulating MMPs as a surrogate for tissue MMPs around clinical events, such as myocardial infarction or in response to therapies affecting extracellular matrix composition.